Hysterectomy by transvaginal natural orifice transluminal endoscopic surgery versus laparoscopy as a day‐care procedure: a randomised controlled trial. (11th December 2018) - Baekelandt, JF; De Mulder, PA; Le Roy, I; Mathieu, C; Laenen, A; Enzlin, P; Weyers, S; Mol, BWJ; Bosteels, JJA
Abstract : Objective: To compare hysterectomy by transvaginal natural orifice transluminal endoscopic surgery (vNOTES) versus total laparoscopic hysterectomy (TLH) as a day‐care procedure. Design: Parallel group, 1:1 randomised single‐centre single‐blinded trial, designed as a non‐inferiority study with a margin of 15%. Setting: Belgian teaching hospital. Population: Women aged 18–70 years scheduled to undergo hysterectomy for benign indications. Methods: Randomisation to TLH (control group) or vNOTES (experimental group). Stratification according to uterine volume. Blinding of participants and outcome assessors. Main outcome measures: The primary outcome was hysterectomy by the allocated technique. We measured the proportion of women leaving within 12 hours after hysterectomy and the length of hospital stay as secondary outcomes. Results: We randomly assigned 70 women to vNOTES ( n  = 35) or TLH ( n  = 35). The primary endpoint was always reached in both groups: there were no conversions. We performed a sensitivity analysis for the primary outcome, assuming one conversion in the vNOTES group and no conversions in the TLH group: the one‐sided 95% upper limit for the differences in proportions of conversion was estimated as 7.5%, which is below the predefined non‐inferiority margin. More women left the hospital within 12 hours after surgery after vNOTES: 77 versus 43%, difference 34% (95% CI 13–56%), P  = 0.007. The hospital stay was shorter after vNOTES: 0.8 versus 1.3 days, mean difference −0.5 days, (95% CI −0.98 to −0.02), P  = 0.004. Conclusions: vNOTES is non‐inferior to TLH for successfully performing hysterectomy without conversion. Compared with TLH, vNOTES may allow more women to be treated in a day‐care setting. Tweetable abstract: RCT: vNOTES is just as good as laparoscopy for successful hysterectomy without conversion but allows more day‐care surgery. Tweetable abstract: RCT: vNOTES is just as good as laparoscopy for successful hysterectomy without conversion but allows more day‐care surgery. This paper includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights15504 .